GAMBARAN TINGKAT PENGETAHUAN MENYIKAT GIGI PADA SISWA KELAS VII SMP N 1 MLATI SLEMAN - Kusuma Wulan Wardani; Susilarti Susilarti; Dwi Eni Purwati (Journal of Oral Health Care, 2017)
Basic Health Research in 2013 showed people’s incorrect habits in brushing teeth which were about 76,6% brushing their teeth each day during morning shower or evening bath due to the lack of knowledge about brushing teeth. Knowledge can be obtained from several factors; they are level of education, occupation, age, socio-economic, experiences, cultural environment, and information. The purpose of this study was to gain deeper more about students’ level of knowledge of brushing teeth in class VII SMP N 1 Mlati Sleman. The research type is descriptive research with cross sectional approach. The subjects in this study were 128 respondents. The variable in this study was a single variable which was the level of knowledge of brushing teeth. The research was conducted in April 2016. The data were collected by using a questionnaire. The analysis of the data presented in the form of cross-tabulations. The results obtained by the level of knowledge aboutbrushing teeth in good criteria (21.9%), moderate (75%) and poor (3.1%). The conclusions obtained most respondents have a better level of knowledge of brushing teeth at the aged 13 years (14.06%), parental education high school (12.5%), parents’ private work (13.3%), parents’ high-income (10.2 %), respondents who ever got counseling (17,18%), and the resources of the electronic media (14.8%).